Can "Conscious Data Contribution" Help Users to Exert "Data Leverage" Against Technology Companies? - Vincent, Nicholas; Hecht, Brent (Proceedings of the ACM on Human-Computer Interaction, 2021)
Tech users currently have limited ability to act on concerns regarding the negative societal impacts of large tech companies. However, recent work suggests that users can exert leverage using their role in the generation of valuable data, for instance by withholding their data contributions to intelligent technologies. We propose and evaluate a new means to exert this type of leverage against tech companies: "conscious data contribution" (CDC). Users who participate in CDC exert leverage against a target tech company by contributing data to technologies operated by a competitor of that company. Using simulations, we find that CDC could be highly effective at reducing the gap in intelligent technologies performance between an incumbent and their competitors. In some cases, just 20% of users contributing data they have produced to a small competitor could help that competitor get 80% of the way towards the original company's best-case performance. We discuss the implications of CDC for policymakers, tech designers, and researchers.